Gender and Employment in the COVID-19 Recession : Evidence on 'She-cessions' - Bluedorn, John.; Caselli, Francesca; Hansen, Niels-Jakob.; Shibata, Ippei (Washington, D.C. : International Monetary Fund, 2021)
Early evidence on the pandemic's effects pointed to women's employment falling disproportionately, leading observers to call a 'she-cession.' This paper documents the extent and persistence of this phenomenon in a quarterly sample of 38 advanced and emerging market economies. We show that there is a large degree of heterogeneity across countries, with over half to two-thirds exhibiting larger declines in women's than men's employment rates. These gender differences in COVID-19's effects are typically short-lived, lasting only a quarter or two on average. We also show that she-cessions are strongly related to COVID-19's impacts on gender shares in employment within sectors.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Aggregate Human Capital; Employment; Intergenerational Income Distribution; Unemployment; Wages